Missing quarterly analyst expectations, CEO turnover and institutional investors - WANG, Juan (Institutional Knowledge at Singapore Management University, 2008)
Research suggests that dedicated institutions, who have concentrated holdings and long-term investment horizon, make management focus less on short-term earnings benchmark. This study presents evidence in terms of CEO career concerns that explains why the management focuses less on short-term firm performance when dedicated institutions hold high levels of ownership. Using quarterly consensus analysts' expectation as a proxy for short-term earnings benchmark, I find that the likelihood CEO turnover is less sensitive to the frequency with which management misses quarterly forecast benchmarks for firms with high dedicated institutional ownership than for firms with low dedicated institutional ownership, suggesting that dedicated institutions reduce pressure on management in terms of career concerns for short-term results and align interests of managers toward long-term firm value creation. This study contributes to the literature on the governance roles of institutions by documenting how institutions affect the sensitivity of CEO turnover decision to firm performance. It has policy implication for business managers and regulators that attracting dedicated institutions alleviates management incentive to play the numbers game to meet quarterly Wall Street expectations.